The artists exile in Mexico and their descendants in the databases. Analysis and proposal - Guasch Marí, Yolanda (Hispania Nova, 2021)
In this article we analyze the existing databases on the network on women artists and the presence in them of the exiles in Mexico after the Spanish conflict; justifying the need to create an online database; in open access; that can be viewed equally form their work and become another space that allows the approach to publications about them; the location of the most representative works or the biography; among other aspects; in order to generate new views that contribute; in short; to your knowledge.